Integrated early childhood development: a challenge for reforms in pre-primary education programme in Nigeria. (2013)
The idea of educating pre-school aged children has been in existence for thousands of years in some countries, while in others, it is relatively new. Pre-primary education has also gained ground in Nigeria since its inclusion in the National Policy on Education (1981), revised 2004) because of its importance. However, government's neglect of children aged 0-3 in the NPE and the uncontrolled private efforts in the provision of pre-primary institutions have made this level of education vulnerable to substandard. This paper has identified some of the lapses in the pre-primary education system particularly the erroneous conception that pre-primary education means early childhood schooling rather than the extent to which pre-primary education school experiences enable them to become enquirers, explorers, investigators and learners. Suggestions on how to make the pre-primary education programme conform to early childhood care and education practices were made.